Health Analysis of Bank Mandiri and Bank BCA with RGEC Method 2010-2014. - Dwi Rahayu; Suhendro Suhendro (Jurnal Ilmiah Wahana Akuntansi, 2016)
This study aims to determine the health level of Bank Mandiri and Bank BCA method RGEC 2010-2014. Descriptive research with quantitative approach. This study assesses the risk profile factors through NPL ratio and LDR, GCG factor, earnings factor through ROA, ROE, NIM and ROA, and the factor of capital through the CAR. Results of the study factors the Bank's risk profile has an average NPL of 2.1%, and the average LDR of 69.56%, while the value of BCA Bank NPL 0.51%, and 67.21% of its value LDR. Factors overall GCG shows the bank is able to meet the eleven aspects of GCG with the average received the title very well. Assessment assessed earnings of ROA, ROE, NIM and ROA Bank BCA has a better rating than the bank. Capital factor assessed with the CAR ratio of Bank Mandiri has an average of 18,06%, while 17,19% of BCA Bank. Thus, if judged by the factor capital, the bank has better performance than the BCA. Keywords: Health of Banks, RGEC